Peningkatan Kepuasan Pasien Melalui Kualitas Pelayanan Dan Loyalitas Pasien Di Rumah Sakit:: Systematic Literature Review - Verolla Ayu Pradita; Vip Paramarta; Kosasih Kosasih; Farida Yuliaty (Universitas Pahlawan Tuanku Tambusai, 2025)
Patient satisfaction is an important indicator in measuring the quality of healthcare services. Patients who are satisfied with the services they receive tend to have a positive view of healthcare facilities and are more likely to return to them for further care. The purpose of this systematic literature review is to determine the quality of healthcare services, patient satisfaction, and patient loyalty. A literature search was conducted through several electronic databases, including Google Scholar and PubMed, to capture articles published from 2020 to June 2025. The article selection process involved several stages of identification and screening based on title and abstract, followed by an assessment of the eligibility of full-text articles based on inclusion and exclusion criteria. All selection stages were documented using a PRISMA flowchart. The results of this study revealed that improving the quality of medical and non-medical services, optimizing administrative processes, effective and empathetic communication, personalizing the patient experience, and utilizing technology to facilitate access are key factors. Building strong and trusting relationships through patient engagement, actively listening to complaints, and offering reward programs are also crucial for fostering loyalty. It can be concluded that improving the quality of healthcare services is crucial because it can drive patient satisfaction, which in turn builds patient loyalty. Satisfied patients are more likely to return and recommend the provider, thereby enhancing the hospital's reputation and financial stability. Keywords: Patient Satisfaction, Service Quality, Patient Loyalty